2013
DOI: 10.1016/j.matdes.2012.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructure on the fatigue properties of Ti–6Al–4V titanium alloys

Abstract: Publisher rights This is the author's version of a work that was accepted for publication in Materials & Design. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Materials & Design, Vol. 46, 04/2013 General rights Copyright for the publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
86
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(99 citation statements)
references
References 28 publications
12
86
0
1
Order By: Relevance
“…The comprehensive study of Wu et al [69] revealed that a finer grain size is able to improve the HCF behaviour of the material, which is consistent with the previously presented understanding with respect to improving crack initiation resistance. However, the long crack growth analysis showed a preference to the lamellar microstructure, particularly with respect to coarser lamellae width.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The comprehensive study of Wu et al [69] revealed that a finer grain size is able to improve the HCF behaviour of the material, which is consistent with the previously presented understanding with respect to improving crack initiation resistance. However, the long crack growth analysis showed a preference to the lamellar microstructure, particularly with respect to coarser lamellae width.…”
supporting
confidence: 86%
“…This is due to the fact that different build directions have the maximum resolved shear direction at different orientations to planes which contain the easiest and most common slip systems [54]. In a comprehensive analysis of the HCF results of wrought Ti-6Al-4V, obtained from 21 different published research results, it was shown by Wu et al [69] that a bimodal microstructure will have superior HCF resistance over a lamellar microstructure, followed by a equiaxed microstructure. Analysis of the primary α content in the bimodal microstructure demonstrated the importance of having a primary α volume fraction of between 30-50% and a primary α size of between 0 and 5 µm to achieve the highest fatigue resistance.…”
Section: Micro-mechanism Contributionmentioning
confidence: 99%
“…Furthermore, it has been discovered that the factors which increase the tensile strength, can also improve the fatigue strength as well (Hosseini, 2012). In addition, in 2013, "effect of microstructure on the fatigue properties of Ti-6Al-4V Titanium alloys" is recommended by Wu et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, titanium alloys (Ti-6Al-4 V, in particular) find extensive applications in the aeronautical, medical, aerospace, chemical, petrochemical, marine, and engineering industries for manufacturing critical systems such as airfoils, undercarriage components, and airframes. [1][2][3][4] However, in spite of these numerous laudable properties, the engineering applications of titanium alloys are often limited due to poor wear resistance, low hardness, high friction coefficient, low hardenability, and the tendency to gall and smear. [5][6][7] It is therefore imperative to develop methods that will remove these limitations, improve and enhance the surface properties of titanium and its alloys while retaining the desirable bulk properties.…”
Section: Introductionmentioning
confidence: 99%